Experimental comparison between speech transmission index (STI) and mean opinion scores (MOS) in rooms - Brachmanski, Stefan (Archives of Acoustics, 2006)
Two methods for assessment of speech quality in rooms were compared: the speech transmissionindex (STI) and mean opinion scores (MOS). Subjective and objective measurementswere carried out in two rooms for different signal to noise ratio within a range from −15 dBAto +15 dBA. The obtained results are shown as a curve describing a relation between a MOS,STI and signal to noise ratio (S/N).